Downregulation of MiR-218 can alleviate high-glucose-induced renal proximal tubule injury by targeting GPRC5A. Issue 6 (2nd June 2020) - Su, Shan-Shan; Li, Bao-Peng; Li, Chun-Lin; Xiu, Fang-Rui; Wang, Dong-Yan; Zhang, Fa-Rong
ABSTRACT: The purpose of this study was to explore the functional implication of microRNA-218 (miR-218) in diabetic nephropathy (DN) through high-glucose-stimulated renal proximal tubule impairment. Biological function experiments showed that miR-218 and inflammatory factors TNF-α and IL-1β were highly expressed in renal proximal tubule under high-glucose conditions. Inhibiting miR-218 alleviated renal tubular cell injury, which was represented by miR-218 inhibitor facilitating renal tubular cell vitality whilst reducing its apoptosis and levels of inflammation factors. In addition, we confirmed that miR-218 directly targeted GPRC5A and negatively regulated its expression. Co-transfection assay showed that overexpression of GPRC5A accentuated the mitigated action of miR-218 inhibitor on renal proximal tubule cell injury induced by high-glucose. Accordingly, these data indicated that downregulation of miR-218 can assuage high-glucose-resulted renal tubular cell damage, and its ameliorative effect was achieved by negative regulation of GPRC5A, which provides a novel direction for unearthing the pathogenesis and even further biological treatment of DN. Graphical abstract: : MiR-218/GPRC5 axis contributes to HK-2 cell viability and apoptosis under high-glucose conditions.